Unfair Trading Practices: Evidence in the Fruit Supply Chain - Katarina Barathova; Jan Pokrivcak; Miroslava Rajcaniova (German Journal of Agricultural Economics (GJAE), 2022)
This paper evaluates the occurrence and determinants of unfair trading practices (UTPs) in the fruit supply chain in Slovakia. Based on a representative survey of fruit growers, mainly apple growers, the study concludes that 79% of the producers experienced at least 1 UTP in a relationship with their main buyer. The most frequent UTPs are late payments (39.6%), payments unrelated to a specific transaction (39.6%), and unilateral changes by buyers in contracts and orders. The results of the probit model show that producer organisations decrease the probability of UTPs relative to conditions in which the main buyer is a private trader (by 32%) or supermarket (by 35%). This result provides some justification for the support of producer organisations under the Common Agricultural Policy of the European Union.
Keywords: 330; fruit; supply chain; survey; unfair trading practices